2007
DOI: 10.1136/jech.2006.056697
|View full text |Cite
|
Sign up to set email alerts
|

Development of a short version of the sense of coherence scale for population survey

Abstract: A three-item sense of coherence (SOC) scale was developed, incorporating the definitions of the three subordinate concepts of SOC for use in population surveys. A cross-sectional internet survey was conducted in the latter part of July 2006. Cronbach's alpha was 0.84. The correlation coefficient of SOC-13 and the newly devised University of Tokyo Health Sociology version of the SOC Scale (SOC-3-UTHS) was 0.51. As regards correlation with a health index, SOC-3-UTHS had a significant association, although this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 7 publications
7
57
0
2
Order By: Relevance
“…However, our data showed an acceptable value (α =0.85). Furthermore, measuring SOC with only three items is recommended for large surveys with limited questionnaire space 8) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our data showed an acceptable value (α =0.85). Furthermore, measuring SOC with only three items is recommended for large surveys with limited questionnaire space 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Responses to each question were scored on a Likert-type scale ranging from 1 to 7, with higher scores indicating stronger SOC. In Japanese studies, the Cronbach's alpha of the SOC-UTHS was ranged from 0.82 to 0.84 7,8) ; furthermore, it was significantly associated with the SOC-13 8) . Psychological distress was evaluated by the 28-item version of the General Health Questionnaire (GHQ) 9) .…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, also for older workers, sense of coherence "can be modified, detrimentally or beneficially, by the nature of the working environment" (p. 165). Many studies have shown this volatility of sense of coherence and the influences of the work environment on its manifestation (Feldt, Kinnunen, & Mauno, 2000;Togari, Yamazaki, Nakayama, & Shimizu, 2007). Antonovsky elaborated on work characteristics that potentially are related to sense of coherence, offering a dense description of a workplace where individuals experience meaningfulness, manageability, and comprehensibility.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, SOC3-UTHS, a three-item, seven-point version of the SOC3 scale, developed by The University of Tokyo Department of Health Sociology, was applied in an extensive multipurpose general population survey (Togari, Yamazaki, Nakayama, & Shimizu, 2007). The reason for this was that whereas many researchers wish to measure sense of coherence within surveys, a 13-item sense of coherence scale cannot always be inserted into questionnaires because of the large space requirement.…”
Section: The Japanese Version Of Sense Of Coherence Scalementioning
confidence: 99%